Activation of PTGS2/NF‐κB signaling pathway enhances radiation resistance of glioma - Cheng Tan; Liang Liu; Xiaoyang Liu; Ling Qi; Weiyao Wang; Guifang Zhao; Libo Wang; Yimeng Dai (Cancer Medicine)
Abstract Objective We focused on the effects of PTGS2/NF‐κB signaling pathway on the radiation resistance of glioma in the study. Methods We downloaded the microarray data from the Gene Expression Omnibus (GEO) database. We verified transfection successfully through QRT‐PCR analysis. Immunofluorescence was used to detect γH2AX content under 2 Gy radiation. The survival rates of cells under 2 Gy irradiation were tested by clonogenic survival assay. Flow cytometry was used to detect cell cycle. Western blot was applied to detect the expression of NF‐κB pathway‐related proteins. We also used MTT assay to detect the proliferation of cells. Results In this research, we discovered that the expression of the PTGS2 was upregulated in radiation‐resistant glioma cells. The radio‐tolerance rate of U87 cells was obviously elevated after the overexpression of PTGS2. The radioresistance of U87R cells was significantly reduced after the knockdown of PTGS2. After radiotherapy, the number of cells arrested in G2/M phase decreased after PTGS2 overexpression in U87cells but increased in PTGS2 knockdown in U87R cells. The survival rate of U87 and U87R cells under radiation decreased significantly after the addition of NF‐κB inhibitor. The proliferation of U87 cells was suppressed by radiation and the addition of Bay 11. In addition, PTGS2 activated NF‐κB signaling pathway and prevented DNA damage after radiotherapy. Lastly, PTGS2 was proved to facilitate tumor cell proliferation and improve the radio‐tolerance. Conclusion PTGS2/NF‐κB signaling pathway was involved in radio‐tolerance of glioma cells, which provided a new insight into glioma therapy.